Transformational leadership, job autonomy and role-breadth self-efficacy : their influence on proactive behaviour in entry-level graduate roles - Minnaar, Heinrich Adrean (School of Management Studies, 2016)
This study investigated the model on the antecedents of proactive behaviour as identified by Den Hartog and Belschak (2012) within the context of entry-level graduate roles (n = 76). A survey was devised which included the use of a five-point Likert-type scale. It was then administered to graduates in entry-level roles in various industries in South Africa to measure the different variables stipulated by the model. When data was analysed, the results revealed that transformational leadership (inspirational), task-related role-breadth self-efficacy (RBSE), and people-related RBSE correlated significantly and positively with proactive behaviour. Transformational leadership (performance) and job autonomy obtained non-significant correlations with proactive behaviour. The results also revealed that job autonomy, task-related RBSE and people-related RBSE did not moderate the relationship between transformational leadership (inspirational or performance) and proactive behaviour. This meant that the display of transformational leadership did not lead to a significant increase in proactive behaviour in low autonomy, low RBSE situations or in high autonomy, high RBSE situations as hypothesised. The unique characteristics of entry-level graduate roles are highlighted by the study - the significance of this model on proactive behaviour in a general employee context potentially may not be relevant to a graduate context. The findings contribute towards research evidence on the development of proactive behaviour in entry-level graduate roles.